2017
DOI: 10.1016/j.anr.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Walking, Muscle Strength, Balance, and Fear of Falling Between Repeated Fall Group, One-time Fall Group, and Nonfall Group of the Elderly Receiving Home Care Service

Abstract: This study suggests that intervention program should be tailored to fall risk factors to enhance gait and balance and lower body muscle strength and reduce the fear of falling to prevent repeated incidences of falls in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 26 publications
7
39
1
3
Order By: Relevance
“…Additionally, our results related to health status showed that several chronic diseases were more prevalent in the fall subgroup compared with the non‐fall subgroup; moreover, it should be mentioned that diabetes and/or comorbidity appeared as other potentially important risk factors but did not reach statistical significance ( p = .066 and p = .067, respectively). Other researchers have found similar results, such as those obtained in prior studies carried out on older populations of distinct ethnicities (Jeon et al, ; Nicklett et al, ; Yang et al, ). As pointed out by Vinik et al (), diabetes is one of the major risk factors for falling due to loss of strength, sensory perception and balance as a consequence of peripheral neuropathy and cognitive deficit.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, our results related to health status showed that several chronic diseases were more prevalent in the fall subgroup compared with the non‐fall subgroup; moreover, it should be mentioned that diabetes and/or comorbidity appeared as other potentially important risk factors but did not reach statistical significance ( p = .066 and p = .067, respectively). Other researchers have found similar results, such as those obtained in prior studies carried out on older populations of distinct ethnicities (Jeon et al, ; Nicklett et al, ; Yang et al, ). As pointed out by Vinik et al (), diabetes is one of the major risk factors for falling due to loss of strength, sensory perception and balance as a consequence of peripheral neuropathy and cognitive deficit.…”
Section: Discussionsupporting
confidence: 82%
“…With regard to sociodemographic characteristics, female gender is identified as an influential risk factor for falls in this population, which is in agreement with previous studies carried out in the Portuguese older population (Moniz‐Pereira, Carnide, Machado, Andre, & Veloso, ; Moniz‐Pereira et al, ). A higher prevalence of falls is also reported in women in other regions of the world (Jeon, Gu, & Yim, ; Lavedán et al, ; Nicklett, Taylor, Rostant, Johnson, & Evans, ), which could be linked to an inherent bone fragility in postmenopausal women caused by osteoporosis, osteoarthritis, obesity and vitamin D deficiency (Ahmadiahangar et al, ; Rezende Cde, Gaede‐Carrillo, & Sebastião, ). For this reason, some countries, such as the United States, recommend screening for osteoporosis in all women ≥65 years and in younger women at increased risk (USPSTF, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, a slight increase in muscle mass was noted in the experimental group, whereas a significant decrease was observed in the control group (t = 2.13, p = 0.046). Existing studies show that limited physical activity in older adults causes muscle atrophy, which, in turn, reduces overall physical function [21,22]. These studies also suggest that physical function in older adults cannot be improved by temporary short-term physical programs, but that it can be improved by consistent long-term physical activity.…”
Section: Discussionmentioning
confidence: 95%
“…Las caídas nos son eventos aleatorios, ocurren en parte debido a deficiencias fisiológicas incluyendo deterioro del equilibrio, debilidad muscular y el enlentecimiento del tiempo de reacción que se da conforme aumenta la edad [4,5] . Así también, las caídas pueden asociarse a disfunción cognitiva; por ejemplo, se postula que una disminución sutil en el funcionamiento cognitivo contribuye a la inestabilidad postural, por lo que el riesgo de caídas aumenta [6,7] .…”
Section: Introductionunclassified